2016
DOI: 10.1542/peds.2016-1658
|View full text |Cite
|
Sign up to set email alerts
|

Respiratory Morbidity After Childhood Burns: A 10-Year Follow-up Study

Abstract: These findings demonstrated increased respiratory infection admissions after burns. These outcomes suggest that immune changes triggered by a burn injury may persist in some children for at least 10 years after wound healing.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
8
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 43 publications
2
8
0
Order By: Relevance
“…It is important to note, however, that such speculation must be confirmed with longitudinal data among adults with well‐healed burn injuries. Lastly, our findings of lower pulmonary function are consistent with findings among children (Duke et al, 2016) and an appreciably smaller cohort of adults with well‐healed burn injuries (Mlcak et al, 1998) several years after injury.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…It is important to note, however, that such speculation must be confirmed with longitudinal data among adults with well‐healed burn injuries. Lastly, our findings of lower pulmonary function are consistent with findings among children (Duke et al, 2016) and an appreciably smaller cohort of adults with well‐healed burn injuries (Mlcak et al, 1998) several years after injury.…”
Section: Discussionsupporting
confidence: 91%
“…Advances in the sub-acute and acute care of burn injuries have improved rates of survival (Porter et al, 2015;Wolf et al, 2018). However, survivors of severe burn injuries are at an increased risk of long-term complications (Peck, 2011;Duke et al, 2015Duke et al, , 2016Duke et al, , 2017Jeschke et al, 2008Jeschke et al, , 2011Stanojcic et al, 2018). Poor respiratory function, as observed in children, following discharge from intensive care (Desai et al, 1993) may contribute to epidemiological findings of low cardiorespiratory fitness and physical activity levels in survivors of severe burn injuries later in life (Dodd et al, 2017;Duke et al, 2017;Ferrando et al, 1997;Ganio et al, 2015;Willis et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…While similar studies are lacking in adults, the observation that even non-severe burn injury is associated with significantly increased risk and severity of infectious diseases and respiratory infections (determined by both admission rates and length-of-stay in hospital) over a follow-up period of around 15 years post-burn injury [ 6 , 8 ], suggests that immune dysfunction is also likely occurring in the adult burn population. The increase in respiratory infections observed in these studies was also observed in paediatric patients after burn [ 13 ], providing further evidence that burn has similar effects on immune function in adults. However, the mechanisms that underlie immune dysfunction in children and adults may not be the same and will be important to investigate in future studies.…”
Section: Introductionsupporting
confidence: 66%
“…A study by the same group of 5,290 Australian children who sustained a first burn revealed that these children had an increased risk of influenza over a 10-year period (IRR 1.78, 95% CI 1.10-2.87), with the highest rates of respiratory tract infections over the first 5 years. 11 Children who sustained a burn demonstrated 1.24 times higher risk for readmission from resulting respiratory tract infection. Amongst the pediatric population, the immune system and lung epithelia are still immature, and it may be that early insult predisposes to impaired future immunity and subsequent infection.…”
Section: Risk Of Influenza Postburn Injury and Evidence For Immunizationmentioning
confidence: 99%